Airway Epithelial Dynamics in Allergy and Related Chronic Inflammatory Airway Diseases - Laulajainen-Hongisto, Anu; Toppila-Salmi, Sanna Katriina; Luukkainen, Annika; Kern, Robert (Frontiers in Cell and Developmental Biology, 2020)
Allergic rhinitis, chronic rhinosinusitis, and asthma are highly prevalent, multifactorial chronic airway diseases. Several environmental and genetic factors affect airway epithelial dynamics leading to activation of inflammatory mechanisms in the airways. This review links environmental factors to host epithelial immunity in airway diseases. Understanding altered homeostasis of the airway epithelium might provide important targets for diagnostics and therapy of chronic airway diseases.